To Be Or Not To Be? What Makes a Child Dyslexic: An Overview on Risk Factors and Correlated Clinical Aspects - Claudio Rosa; Carlo Aleci (Archives of Current Research International, 2020)
Developmental dyslexia, one of the most common neuro-developmental disorders, is frequently under-diagnosed or diagnosed late. Despite there is consensus on the neurobiological and genetic basis and on the environmental influence, the multi-faceted aspects of dyslexia and the complexity of its phenotypic expression hinder the identification of the risk factors. Indeed, determining risk factors and understanding how they predispose to the reading disability is important for an early diagnosis and a satisfactory rehabilitative outcome. The aim of this paper is therefore to provide an overview on the genetic, biochemical, anatomical and environmental variables involved in the pathogenesis of developmental dyslexia, and on the visual-perceptual aspects that characterize children who struggle to read.